Using Very Large Corpora to Teach Modern English (1500–1945) - Smitterberg, Erik (Nordic Journal of English Studies, 2023)
This article describes the incorporation of a corpus-based research assignment in a 7.5-credit Master’s-level module on Early and Late Modern English. The design of the module as a whole as well as of the research assignment is discussed, and it is shown how this design tallies with intended learning outcomes based on Bloom’s revised taxonomy. I also suggest ways in which students with little previous experience of corpus-based research can be introduced to the use of very large corpora relatively quickly with the aid of, among other things, exercises and pre-recorded lectures. A key component of the research assignment concerns methodological desiderata such as ensuring recall and precision in corpus-based retrieval of historical features, operationalizing frequency appropriately, taking into account the influence of the genre parameter, being mindful of the limitations of the corpus used, and citing and evaluating secondary sources. Students learn about the value of these desiderata largely through data-driven learning before and during their work on the assignment; examples of how they have been addressed in individual papers are provided. Finally, the value of including empirical, corpus-based components in a historical course is discussed.